C–H activation derived CPPs for photocatalytic hydrogen production excellently accelerated by a DMF cosolvent. Issue 42 (13th September 2019) - Huang, Wei-Ya; Shen, Zhao-Qi; Cheng, Jing-Zhao; Liu, Li-Lin; Yang, Kai; Chen, Xirong; Wen, He-Rui; Liu, Shi-Yong
Abstract : An atom-economic synthetic method is developed to access CPP materials used for photocatalytic H2 production from H2 O, and the PHP reaction can be greatly accelerated by DMF cosolvent, leading to an HER of 15 975 μmol g −1 h −1 without the aid of Pt. Abstract : A series of four conjugated porous polymer CPPs (CPs1–4 ) with various geometries have all been readily synthesized via direct C–H arylation between bithiophene (BT) and 1, 3, 6, 8-tetrabromopyrene (TBPy), 2, 2′, 7, 7′-tetrabromo-9, 9′-spirofluorene (TBSF), 1, 3, 5-tribromobenzene (TBB) and 1, 4-dibromobenzene (DB) respectively. The photocatalytic hydrogen evolution from water splitting by these CPPs under visible light irradiation is studied in detail. An amazing hydrogen evolution rate (HER) of 95.85 μmol h −1 was successfully achieved by the four-directional Py-BT-based CPP (CP1, 6 mg), using ascorbic acid (AA) and N, N -dimethylformamide (DMF)/water as a sacrificial agent and co-solvents respectively. Such a HER value is 8-fold higher than that of applying commonly used MeOH/water as a co-solvent in the same photocatalytic system. Significantly, when a 0.5 wt% platinum (Pt) co-catalyst was added into the above photocatalytic system, an unprecedented HER of 184.86 μmol h −1 (6 mg) was further realized. The combination of atom-economically synthesized CPPs and accelerating the HER by means of simply tuning the composition of co-solvents provided herein represents a promising step toward accessing green energy by green chemistry.